2022
DOI: 10.3389/fitd.2022.957166
|View full text |Cite
|
Sign up to set email alerts
|

Malaria and anemia in children under 7 years of age in the western region of Côte d’Ivoire

Abstract: BackgroundAnemia is a major public health problem, affecting nearly one-quarter of the world’s population. It is defined as a reduction in the hemoglobin level in the peripheral blood to below the normal threshold set for a particular population. Very often in the subtropics, helminths or malaria co-infect an individual, causing morbidities that vary by age and region. This study aims to characterize the type of anemia observed in children under 7 years of age infected with malaria in the western region of Côt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…It was seen in 88% of children. In the study of Ehouman et al 11 authors concluded that iron deficiency anemia as most common entity in microcytic hypochromic anemia. In the study done by Srinivas Madhuri et al 12 among 316 children aged 2 months to 4 years, it was found that 58% of children were anemic due to iron deficiency anemia and 5 % had megaloblastic anemia-marcocytic or normocytic normochromic anemia.…”
Section: Discussionmentioning
confidence: 99%
“…It was seen in 88% of children. In the study of Ehouman et al 11 authors concluded that iron deficiency anemia as most common entity in microcytic hypochromic anemia. In the study done by Srinivas Madhuri et al 12 among 316 children aged 2 months to 4 years, it was found that 58% of children were anemic due to iron deficiency anemia and 5 % had megaloblastic anemia-marcocytic or normocytic normochromic anemia.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9]. Recently, several cases of mixed infection of P. falciparum and P. malariae specires were also reported by Ehouman et al, [10] in the Western region of the country.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent intensity was moderate anemia (64.4%), followed by mild (34.4%) and severe (1.6%), with microcytic hypochromic anemia at a frequency of 55.6%. The observation of this anemia can be explained by the fact that at this age [2-6 years], children are most of the time walking or playing in various external environments where there are supplementary foods such as nuts and seeds, fruits and extra vegetables to grab in addition to the family food shared together usually [46]. These additional micronutrients would provide them with the iron balance needed to reduce their absolute iron deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…In Côte d'Ivoire, the prevalence of intestinal schistomiasis (S. mansoni) in 2016 was estimated at more than 22.1% and 23.2% in school-aged children and adults population respectively [8][9] and that of anemia at 55.0% [10].…”
Section: Introductionmentioning
confidence: 99%